Heatlh reproduction in teenager Pengaruh Penyuluhan Gizi Masa Prakonsepsi Terhadap Perilaku Pemenuhan Gizi Wanita Usia Subur di Kecamatan Talibura - Eusabia Liansiani Ledor (Gema Bidan Indonesia, 2021)
Nutrition in the preconception period is the main factor affecting the condition of women of childbearing age in pregnancy and the well-being of the baby. The purpose of this study is to determine the effect of nutrition counseling in the preconception period on the knowledge, attitudes and actions (practices) of fulfilling the nutrition of women of childbearing age. This research is an experimental study with a quasy experiment pre post test design with control group design. Sampling using purposive sampling technique.Total sample of 30 women of childbearing age divided into 2 groups, namely the intervention group and the control group. The intervention group was given the preconception period nutritional counseling treatment while the control group was not given the treatment. Data collection using questionnaires. The results of the study obtained the influence of changes in knowledge, attitudes and actions (practices) of fulfilling nutrition after being given nutritional counseling. Analysis using the Wilcoxon test obtained knowledge of p value = 0.001, attitude of p value = 0.002 and action value of p = 0.001 where the value of p<0.05 showed that there was an influence before and after nutritional counseling. The results of the Mann Withney value of p<0.05 indicated differences in the behavior of the intervention group and control group after being given counseling. Nutrition counseling in the preconception period can increase knowledge, influence the attitude of women in a positive direction, and improve the ability of women to prepare and consume nutritionally balanced foods.